2019
DOI: 10.1111/tra.12628
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of G protein‐coupled receptor signaling by plasma membrane organization and endocytosis

Abstract: The trafficking of G protein coupled‐receptors (GPCRs) is one of the most exciting areas in cell biology because of recent advances demonstrating that GPCR signaling is spatially encoded. GPCRs, acting in a diverse array of physiological systems, can have differential signaling consequences depending on their subcellular localization. At the plasma membrane, GPCR organization could fine‐tune the initial stages of receptor signaling by determining the magnitude of signaling and the type of effectors to which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 116 publications
(229 reference statements)
1
47
0
Order By: Relevance
“…Next, we addressed the CME downstream intracellular mechanism leading to YAP1 cytoplasmic redistribution and transcriptional reprogramming. Active endocytosis not only regulates PM SA in cells, but is also essential for controlling the surface distribution of a wide-range of membrane proteins including surface receptors and transporters (Antonescu et al, 2014;Bokel and Brand, 2014;Weinberg and Puthenveedu, 2018). Recent studies have suggested that surface expression of glucose transporters and the levels of cytoplasmic glucose can control YAP1 localization and activity (Santinon et al, 2015;Zhang et al, 2018).…”
Section: Increased Cme Upon Cell Fusion Results In Transient Glucose mentioning
confidence: 99%
“…Next, we addressed the CME downstream intracellular mechanism leading to YAP1 cytoplasmic redistribution and transcriptional reprogramming. Active endocytosis not only regulates PM SA in cells, but is also essential for controlling the surface distribution of a wide-range of membrane proteins including surface receptors and transporters (Antonescu et al, 2014;Bokel and Brand, 2014;Weinberg and Puthenveedu, 2018). Recent studies have suggested that surface expression of glucose transporters and the levels of cytoplasmic glucose can control YAP1 localization and activity (Santinon et al, 2015;Zhang et al, 2018).…”
Section: Increased Cme Upon Cell Fusion Results In Transient Glucose mentioning
confidence: 99%
“…TyrRII has previously been shown to be broadly responsive to a variety of monoamines and, given that monoamine release is generally associated with arousal [46][47][48][49], this system could represent an elegant mechanism for astrocytes to track wakefulness and consequently homeostatic sleep need. Because monoaminergic receptor expression is often tightly regulated by diverse signaling mechanisms [50], we examined whether tyrRII expression varied according to sleep need. We assessed astrocyte expression of tyrRII mRNA using TRAP-qPCR (Translating Ribosome Affinity Purification followed by Quantitative PCR) [51], which we performed by expressing eGFP-RpL10a in astrocytes and immunopurifying actively translating mRNA using magnetic beads coated with anti-GFP antibodies ( Figure 5A).…”
Section: Tyrrii Is Upregulated With Sleep Loss and Participates In A mentioning
confidence: 99%
“…i) Endosomal involvement: The importance of GPCR signaling from endosomal/intracellular compartments (Hanyaloglu 2018;Weinberg et a, 2019), needs to be understood in depth so that appropriate therapeutic targets can be designed.…”
Section: Supplementarymentioning
confidence: 99%